A study of mathematics teacher identity as shaped through participation in a mathematics teacher professional development programme - Kangela, Nyameka (Rhodes University, Faculty of Education, Department of Education, 2017)
There is an abundance of evidence suggesting that all is not well in mathematics education in South Africa. It is also common cause that the role of mathematics teachers is central to finding sustainable solutions to what is commonly referred to as a mathematics crisis. The purpose of this study is to explore the process of change in selected mathematics teachers' identities as they participated in a mathematics teacher Professional Development Programme (PDP) at Rhodes University. The core of the PDP was a teacher enrichment programme called the Mathematics Teacher Enrichment Programme (MTEP), under the aegis of the First Rand Foundation (FRF) Mathematics Education Chair at Rhodes University. MTEP foregrounded and emphasized the teaching of mathematics for conceptual understanding. The research approach was qualitative, and it used elements of the methods associated with educational ethnography. The data was collected from five teachers from five different schools that participated in the FRF Maths Chair project. I used Wenger's (1998) three modes of belonging to analyse the identities of the five participants. This was achieved through analysing the teachers' practice with a particular focus on teaching for conceptual understanding. I used Sfard & Prusak's (2005) framework to analyse the participants' journey from an actual to a designated identity through their participation in MTEP. The participants' changing sense of belonging to MTEP was a key element in transforming their practice to teaching for conceptual understanding. I assumed the role of a participant observer during MTEP sessions, and of an outside observer as a researcher.The study found that the selected teachers' participation in the MTEP community of practice strongly encouraged them to accumulate shared histories of learning and teaching. The study found that as participating teachers adopted and grew into their designated identity they partially embraced and implemented a conceptual teaching approach. The gap between their actual and their designated identity was partly closed as they sought to align their teaching with MTEP's goal of conceptual teaching.
Keywords: Mathematics Teacher Enrichment Programme (MTEP) (Rhodes University); Mathematics teachers -- Psychology; Mathematics teachers -- Psychology -- Case studies; Mathematics teachers -- Training of -- South Africa